Rancang Bangun Sterilisasi Autoclave Menggunakan Metode Dry Heat Arduino Uno Pada Alat Kedokteran Gigi (Universitas Darul Ulum, 2025)
Sterilization is an important process in dentistry to ensure that the instruments used are free from pathogenic microorganisms. This study aims to design and build an Autoclave sterilization system using the dry heat method based on Arduino Uno. This system is designed to provide an effective and efficient solution in the sterilization process of dental instruments. The method used in this study involves designing hardware and software integrated with Arduino Uno. The hardware consists of heating elements, temperature sensors, and control systems designed to regulate temperature accurately and consistently. Sterilization of dental instruments is very important to maintain cleanliness and prevent cross-infection. This final project is entitled